Characterization of Stx2 tubular response in a rat experimental model of hemolytic uremic syndrome - Ochoa, Federico Claudio (2010)
In Argentina, hemolytic uremic syndrome (HUS) constitutes the most frequent cause of acute renal failure in children. The aim of our study was to analyze the early tubular response under the effect of Shiga toxin type 2 (Stx2) in a rat experimental model of HUS. METHODS: Adult male Sprague-Dawley rats were injected intraperitoneally with culture supernatant from recombinant Escherichia coli expressing Stx2. Functional, histological, immunohistochemical and Western blot studies were performed at 48 h postinoculation. RESULTS: Renal tubules showed the loss of the epithelial markers E-cadherin and beta-catenin, and an increase in transforming growth factor-beta1 expression. We detected the expression of alpha-smooth muscle actin in the interstitium and fibrosis in the periglomerular areas. CONCLUSION: Our results indicate that the early tubular response to the effects of Stx2 is related to an immunophenotype change of tubular cells and the presence of mild fibrosis in the interstitium.